2020
DOI: 10.3390/antiox9030234
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antidepressant Effects of Scutellaria baicalensis, Hericium erinaceus and Rhodiola rosea

Abstract: Recent studies focused on the pharmacology and feasibility of herbal compounds as a potential strategy to target a variety of human diseases ranging from metabolic to brain disorders. Accordingly, bioactive ingredients which are found within a variety of herbal compounds are reported to produce both neuroprotective and psychotropic activities which may help to combat mental disorders such as depression, anxiety, sleep disturbances and cognitive alterations. In the present manuscript, we focus on three herbs wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 177 publications
(403 reference statements)
0
30
0
4
Order By: Relevance
“…The two major flavonoids of Scutellaria baicalensis , baicalein and its aglycone metabolite baicalin, possess widespread biological activities, including anti-bacterial, anti-viral, anti-inflammatory, anti-oxidant, neurotrophic, and neuroprotective effects [ 67 , 230 ]. Baicalein and baicalin show inhibitory effects on various strains of influenza virus and SARS-CoV, both in vitro and in vivo.…”
Section: Anti-viral and Anti-inflammatory Effects Of Phytochemicalmentioning
confidence: 99%
“…The two major flavonoids of Scutellaria baicalensis , baicalein and its aglycone metabolite baicalin, possess widespread biological activities, including anti-bacterial, anti-viral, anti-inflammatory, anti-oxidant, neurotrophic, and neuroprotective effects [ 67 , 230 ]. Baicalein and baicalin show inhibitory effects on various strains of influenza virus and SARS-CoV, both in vitro and in vivo.…”
Section: Anti-viral and Anti-inflammatory Effects Of Phytochemicalmentioning
confidence: 99%
“…Additionally, Hericium erinaceus has also been shown to improve the hippocampal-dependent recognition memory with enhancement of neurotransmission and neurogenesis in the hippocampus and the cerebellum 13 , 20 . Recent in-vivo and clinical studies in early cognitive decline and depression suggest it has the potential to ameliorate cognitive and neurological deficits 21 – 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that baicalin has a polyphenolic hydroxyl structure and prevents glyoxal-induced cystatin aggregation by affecting its aggregation process, which opens a new way for the treatment of protein misfolding diseases [ 75 ]. In addition, baicalin extract has potential applications in the fields of anti-fibrosis, anti-cancer, anti-aging, anti-depression, and immune regulation [ 76 , 77 , 78 , 79 , 80 ].…”
Section: Biological Functions Of S Baicalensismentioning
confidence: 99%